2021
DOI: 10.12973/eujem.4.1.35
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Transformational Leadership, the Cultural Intelligence of Teachers and the Skills of Principals’ Diversity Management

Abstract: <p style="text-align: justify;">It is regarded as considerable values those principles’ skills of managing diversities and teachers’ cultural intelligences which mean they understand and appreciate other cultures. These core values are remarkably vital to be culturally literate in the global world. The organizations and their administrators respecting the diversities of the employees can allocate more time competing their counterparts in the world instead of losing energy with unnecessary conflicts. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Gokalp et al concluded that middle school teachers had a moderate (average) level of cultural intelligence. Moreover, Cobanoglu (2021), who undertook a study on the cultural intelligence levels of teachers, determined that teachers' level of cultural intelligence was "generally high". Furthermore, in the study done by Sengul (2018) it was concluded the cultural intelligence levels of teacher candidates were high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gokalp et al concluded that middle school teachers had a moderate (average) level of cultural intelligence. Moreover, Cobanoglu (2021), who undertook a study on the cultural intelligence levels of teachers, determined that teachers' level of cultural intelligence was "generally high". Furthermore, in the study done by Sengul (2018) it was concluded the cultural intelligence levels of teacher candidates were high.…”
Section: Discussionmentioning
confidence: 99%
“…When the literature is analyzed, some studies that provide suggestions for increasing cultural intelligence have been found. In his research, Cobanoglu (2021) suggested providing the teachers with information about different cultures, ensuring that they understand the differences, and creating motivation for learning different cultures. Besides, Goksoy (2016) suggested that cultural intelligence levels of administrators who will be assigned to administrative roles in educational organizations should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Plutzer (2021) examined how cultural intelligence impacts multicultural team effectiveness, highlighting the strong relationship between motivational and metacognitive aspects of cultural intelligence and team effectiveness. Cobanoglu (2021) investigated the relationship between transformational leadership, teachers' cultural intelligence, and principals' diversity management skills, emphasizing the importance of cultural intelligence in enhancing transformational leadership. Kozikoglu & Tosun (2020) studied teachers' opinions on culturally responsive pedagogy and their cultural intelligence levels, finding a moderate, positive relationship between them.…”
Section: Studies Related To Cultural Intelligencementioning
confidence: 99%
“…Despite the valuable contributions made by recent studies on cultural intelligence, several research gaps warrant further investigation. First, while studies such as those by Cobanoglu (2021) and Kozikoglu & Tosun (2020) have examined the relationship between cultural intelligence and leadership or pedagogical practices, there is a need for more comprehensive research on the specific mechanisms through which cultural intelligence influences these domains. Furthermore, although studies like Plutzer (2021) have explored the impact of cultural intelligence on team effectiveness, there is limited research on how cultural intelligence interventions or training programs can be effectively implemented to enhance organizational outcomes, like organizational health.…”
Section: Studies Related To Cultural Intelligencementioning
confidence: 99%
“…Cultural intelligence, which has become one of the key elements of organizational productivity with globalization, means the ability of an individual to communicate, act and be successful in culturally diverse environments . Cultural intelligence consists of four dimensions: Metacognitive cultural intelligence, cognitive cultural intelligence, motivational cultural intelligence, and behavioral cultural intelligence (Earley & Ang, 2003;Cobanoglu, 2021). Metacognitive cultural intelligence, which is the most abstract of these dimensions, is the ability of an individual to create strategies when encountering different cultures and to use cultural understanding to solve culturally complex problems.…”
Section: Introductionmentioning
confidence: 99%